Resepsi Gen Z pada Konten Podcast Denny Sumargo berjudul “PENULIS CONTEKAN PRESIDEN, JOKOWI TIDAK LEBIH BAIK DARI PRESIDEN SEBELUMNYA⁉️- Tom Lembong” - Afandi, Muhammad Rizki; Rozi, Fakhrur (Tapis: Jurnal Penelitian Ilmiah, 2024)
A podcast is a kind of YouTube content that is now quite popular in Indonesia and is a popular communication form among Indonesian YouTubers, such Denny Sumargo. “PENULIS CONTEKAN PRESIDEN, JOKOWI TIDAK LEBIH BAIK DARI PRESIDEN SEBELUMNYA⁉️- Tom Lembong " was one of Denny Sumargo's most popular podcasts. Researchers discovered that individuals replied to the video in talks that aroused their interest as well as in the podcast's comments section hosted by Denny Sumargo. Some of Generation Z. Based on the many remarks made by friends in Generation Z, it's intriguing to consider how the audience would react to the content or message the video conveys. Qualitative research methodologies are used in this study. The method used is Stuart Hall's encoding/decoding model's reception analysis method, which results in a staging of meaning into three categories: Dominant Position, Negotiated Position, and Oppositional Position. Data sources included secondary data gleaned from other library resources as well as original data gathered by observation, interviews, and documentation. The results of the analysis of Gen Z's reception of Denny Sumatgo's podcast based on Stuart Hall's reception analysis show that most of the three informants are in the Dominant Position, which is characterized by agreement with the communicator's message and understanding of its denotation and connotation meanings.